Ensuring the security of the banking system on the basis of innovative metaspace technologies - Kushnir, Svitlana; Sakhno, Liudmyla; Kostornoi, Serhii (Актуальні питання економічних наук, 2026)
The article reveals scientific and applied aspects of ensuring the security of the banking system based on innovative metaspace technologies. Modern trends in the development of the banking system in the context of the active implementation of Blockchain technologies, Big Data and digital financial platforms are studied. It is established that the rapid spread of digital banking services, VR/AR technologies and decentralized financial systems is accompanied by increased cyber risks, an increase in the number of digital frauds, data leaks and threats to the information security of banking institutions. The need to form a comprehensive system for protecting banking infrastructure based on modern metaspace technologies is substantiated. The purpose of the article is to study the strategic directions of ensuring the security of the banking system based on innovative metaspace technologies and to determine the impact of modern cyber threats on the functioning of financial institutions in the process of integrating Blockchain and AI technologies into banking activities. Particular attention is paid to the use of Blockchain technologies to ensure the transparency of financial transactions and monitor cyber risks, protect digital infrastructure and smart contracts to minimize the risks of financial fraud. The research methods are based on the use of a systematic approach to assessing the security of the banking system, methods of comparative analysis, statistical generalization, economic modeling and graphic visualization of research results. To assess the trends in the development of digital banking and the level of cyber threats, methods of dynamic analysis of statistical indicators were used.The results of the study showed that during 2020-2024, there was a significant increase in the volume of digital banking transactions due to the activation of the metaspace platform in the banking system.It was found that the increase in the level of digitalization of the banking system is accompanied by a simultaneous increase in the number of cyber incidents, phishing attacks, software-on-demand threats and cases of compromise of digital assets. It was proven that traditional banking infrastructure protection systems do not provide a sufficient level of security. At the same time, it was determined that in the context of the development of innovative metaspace technologies, as a decentralized financial platform, Blockchain, AI, secure cloud services and biometric identifiers are being integrated into the banking system in order to increase the level of protection of financial transactions, ensure the transparency of digital transactions and minimize the risks of unauthorized access to banking transactions. A strategy for ensuring the security of the banking system based on innovative metaspace technologies is proposed, which involves the formation of a multi-level cyber protection system, the development of the digital infrastructure of banks, the implementation of AI-risk monitoring and the adaptation of regulatory policy to the conditions of metaspace development. The conclusions show that the use of innovative metaspace technologies in the banking system security system contributes to increasing its cyber resilience by reducing the level of digital risks and ensuring the stability of banking activities in the conditions of digitalization of the economy. The implementation of the proposed strategy will allow to ensure effective protection of banking data, minimize financial losses from cyber threats and increase the level of customer trust in digital banking services. Further research should be directed at the development of adaptive models of cyber risk management, improving mechanisms for regulating the financial platform of metaspace and forming international standards for digital security of the banking system.